Representations of femininity in advertising: stereotypes, disruptions, and flaws - Freire Oliveira-Cruz, Milena (2017)
This article aims to map the different ways in which femininity is currently represented in advertising in Brazil: the reproduction of stereotypes reinforcing gender inequalities as well as the disruption of established models by mean of valuing women’s autonomy. By drawing on data that demonstrate the public’s questioning of female standards and the impact of advertisements seen as sexist by their audiences, we intend to reflect on the relation established between advertising and society as well as highlighting the need to reconfigure the ways for reflecting on and representing gender issues in advertising.